IMPROVING STUDENTSâ ABILITY IN VOCABULARY MASTERY THROUGH INDEX CARD MATCH - Khairul Anwar, Diah Astriyanti, (Edukasi: Jurnal Pendidikan, 2016)
The purpose of this research is to find out of how well Index Card Match strategy can Improve studentsâ ability in vocabulary mastery in the first grade of MTs Hidayatus Shibyan students of P.Naâim Sui.Ambawang Kubu Raya. The method used in this research was a Classroom Action Research (CAR) which consisted of Planning, Acting, Observing, and Reflecting. This research was conducted in two cycles in order to get maximum result of the research. In cycle 1, the quantitative data showed that the students mean score was 65,20 and in cycle 2 the mean score was 75,30. Based on the minimum of standard achievement (KKM), that is 70, the mean score of the second cycle was showed improvement from the first cycle. It showed that the students got improvement and past the KKM. In The qualitative data describe that the students become more often in asking the question to the teacher, especially in cycle 2. The students seems to motivated to find more vocabulary related to the topic given. This is indicate that the use of Index Card Match improved the students vocabulary mastery and make the students become more active and motivated to improve their vocabulary. In conclussion, the studentsâ problem in their vocabulary mastery could be successfully solved through Index Card Match Strategy.Â Keywords: Vocabulary,Index card Match Strategy,Classroom Action Research